2023
DOI: 10.1111/bjh.18779
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cell transplantation for hepatitis‐associated aplastic anaemia and non‐hepatitis‐associated aplastic anaemia: A propensity score‐matched analysis

Abstract: To validate the efficacy and safety of haematopoietic stem cell transplantation (HSCT) in hepatitis-associated aplastic anaemia (HAAA) patients, we reviewed 260 patients who underwent HSCT for acquired aplastic anaemia and eventually included 30 HAAA patients and 90 non-HAAA patients using propensity score matching. In the HAAA group, the estimated 5-year overall survival rate (75.8% vs. 86.5%, p = 0.409), failure-free survival (FFS) rate (74.0% vs. 83.2%, p = 0.485), graftversus-host disease (GVHD)-free FFS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Unfortunately, the conditioning regimen is significantly different between the historical control group and the ruxolitinib group (Supplementary Table 1 ) whereby higher proportion of the historical cohort used ALG (64.47% vs 42.86) and FAC (39.47% vs 14.29%) as conditioning regimen. We thus performed propensity score matching [ 29 ] to minimize the effects of confounding factors resulting in 35 patients in the historical-matched-control group (hereafter refer to control group). The matched patients were not significantly different in terms of baseline characteristics compared to ruxolitinib group, which are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the conditioning regimen is significantly different between the historical control group and the ruxolitinib group (Supplementary Table 1 ) whereby higher proportion of the historical cohort used ALG (64.47% vs 42.86) and FAC (39.47% vs 14.29%) as conditioning regimen. We thus performed propensity score matching [ 29 ] to minimize the effects of confounding factors resulting in 35 patients in the historical-matched-control group (hereafter refer to control group). The matched patients were not significantly different in terms of baseline characteristics compared to ruxolitinib group, which are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Two differentially distributed variables i.e., conditioning regimens (regimen w/o Bu) and ATG types (rATG or pALG) were Included in the propensity score matching (PSM) analysis to identify patients from historical cohort to match the ruxolitinib cohort. A 1:1 nearest neighbor matching with a caliper width of 0.2 [ 29 ] with significance level at P < 0.05 were adopted.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, only one study conducted by the Japan Society for Haematopoietic Cell Transplantation 16 reported a 5-year overall survival (OS) rate of 86.0% and a 100-day cumulative incidence of grade II–IV acute graft-versus-host disease (aGVHD) at 11.1% among HAAA patients who received HSCT from HLA-identical donors. In our published article 4 , we conducted a comparative analysis, matching 30 patients who underwent HAAA procedures at our center with patients without HAAA. The findings showed that estimated 5-year OS rate (75.8% vs. 86.5%, P = 0.409) and FFS rate (74.0% vs. 83.2%, P = 0.485) after HSCT were slightly lower but not statistically significantly different from those in the non-HAAA group.…”
Section: Discussionmentioning
confidence: 99%
“…Its pathogenesis remains poorly understood. Previous studies 2 4 have shown that HAAA is more prevalent in adolescent males, and most patients do not exhibit evidence of active hepatitis A, B, C, D, E, G and Torque Teno virus during diagnosis. Both HAAA and non-viral hepatitis may share a common etiology, which is mainly T-cell mediated immune dysregulation.…”
Section: Introductionmentioning
confidence: 91%